INDUSTRI KREATIF PADA FENOMENA GAME ONLINE - RR Ella Evrita H, S.E, M.M, RR Ella Evrita H, S.E. M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
The creative economy is an economic era that prioritizes creativity to create higher added value or benefits and is driven by the creative industry, in which there is a group of interactive games. Method The research was conducted using a qualitative method, which in principle is a review that plans to understand the tricks experienced by the subject. Based on the objectives, the development of interactive games for the 2015–2019 period will focus on interactive games with the following objectives: 1). Educational, 2). Advertising, 3). Serious games, 4). Casual games. What is happening now is that the phenomenon of the development of casual games in society, especially the younger generation, is more prominent. There are 3 goals that should be a priority for development in the community. How can the four goals in this interactive game develop and become one of the drivers of economic growth, especially the creative economy in Indonesia? What about online games that exist today, can they become a new business in Indonesia? How to develop the business? How to prevent that must be done so that the negative impact on online games does not enlarge. Method The research was conducted using a qualitative method, which in principle is a review that plans to understand the tricks experienced by the subject. The definition of qualitative research itself is found in several literatures.